ANALYSIS OF HYDROPONIC VEGETABLE BUSINESS IN SONOKWIJENAN SUKOMANUNGGA SUB-DISRICT SURABAYA - Jubandi, Hendrikus; Susanto, Heri; Dianto, Andri Krisna (Jurnal Agribisnis Wijaya Putra Surabaya, 2022)
This study aims to determine the cost structure of hydroponic vegetable business in Sonokwijenan village, to determine business revenue and also to determine the advantages and efficiency of hydroponic vegetable business in Sonokwijenan village. The study was conducted from June to July 2020. The results showed that (1) The percentage of total fixed costs to the total cost of each vegetable commodity ranged from 60-71 percent, while the percentage of total variable costs to total costs ranged from 29-38 percent . Fixed costs consist of land rent, nursery greenhouse depreciation, enlargement greenhouse depreciation, irrigation facilities depreciation, equipment depreciation, permanent labor, electricity, distribution. The variable costs incurred consist of daily labor costs, costs for using seeds, rockwool, nutrition, and packaging. The highest fixed cost components are fixed labor costs and distribution costs, while the highest variable cost components are daily labor costs. (2) The calculation of the revenue received by a business is influenced by the selling price of the commodity and the amount that can be sold or the value obtained from the commodity. The largest total revenue obtained by the Sonokwijenan sub-district, Surabaya is kale with a total revenue of 126,350,000. (3) hydroponic water spinach commodity is the most efficient and profitable commodity compared to other hydroponic vegetables with an R/C ratio value of 2.42, this is because kale uses the gravel substrate method which can save more costs.